PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP SELF-DISCLOSURE SISWA - Nurul Fauziah; Titik Haryati (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the significance of self-disclosure among students of SMP NEGERI 20 in East Jakarta who use gadgets. Gadgets have a significant influence on changing the behavior of their users in this advanced technological era. The population used in this research consisted of eighth-grade students from SMP NEGERI 20 in Jakarta, with a total of 48 students from 9 classes, where each class had 5-6 students. The sampling technique used in this study was simple random sampling. Data collection was done using a Likert scale, and the prerequisites for analysis, such as normality, linearity, and hypothesis tests, were conducted. The results of the field research on the influence of gadget usage intensity on self-disclosure showed that there is a significant effect of the variable (X) on the variable (Y). This can be seen from the significance value of 0.014 < 0.05. Therefore, it can be interpreted that the alternative hypothesis (Ha), which states that gadget usage intensity has an influence on self-disclosure, is supported. The variable of gadget usage intensity accounts for 1.24% of the variance, while the remaining variance is influenced by other variables not included in the model that can affect self-disclosure.